The Prevalence of Severely Increased Albuminuria in the Type 2 Diabetes Population with Chronic Kidney Disease of Low Socioeconomic Status in San Juan: A Population in Need of Improved Accessibility to Disease-Modifying Therapy - Irizarry-Villafañe, Gabriel I.; González-Bóssolo, Alex (Puerto Rico Health Sciences Journal, 2023)
Objective: The aim of this study was to determine the prevalence of severely increased albuminuria and the percentage of patients with the indication for canagliflozin in the type 2 diabetes population with chronic kidney disease (CKD) and low socioeconomic status in the San Juan City Hospital. Methods: This cross-sectional study examined the electronic records of 129 Hispanic type 2 diabetes patients. CKD in this population was defined according to the most recent nephrology and endocrinology guidelines. Albuminuria was diagnosed with two positive urine albumin/creatinine ratio results within 3-6 months. Data was obtained from July 2017 to January 2020 and analyzed utilizing descriptive statistics and correlations. Results: The prevalence of moderately and severely increased albuminuria in patients with type 2 diabetes and CKD were 51.2% and 18.6% respectively. The number of patients with type 2 diabetes who filled the FDA indication for canagliflozin were 16.3%. The prevalence of hypertension, coronary artery disease (CAD) and heart failure (HF) was 61.2%, 15.5% and 10.1% respectively. Between albuminuria severity and decreased renal function, a tendency was observed although not statistically significant (r = -0.14, 95% CI: -0.31, 0.03; P = 0.109). While evaluating association between albuminuria groups and CAD, there was a noticeable tendency close to reaching statistical significance (P = 0.060). Conclusion: There is a scarcity of studies regarding the prevalence of severely increased albuminuria in type 2 diabetics with CKD and this study contributes to the literature. On analysis of associations, statistical significance not reached likely due to small sample size.